Evolution of economic governance in the European Monetary Union - Attard Silvio; Demarco Alexander (Central Bank of Malta, 2013)
This note provides an account of the major milestones in the evolution of the economic governance in the European monetary union, assessing the reforms in governance frameworks of the EMU from 1997 up to mid-2013. It mainly focuses on the post-2010 reforms, where the financial crisis and the ensuing sovereign debt crisis exposed the weakness of the economic governance framework of EMU in Europe. It also highlights the on-going proposals for further coordination and cooperation that have been brought forward but still require agreement among Member States. The note suggests that while the commitment shown to introduce stricter fiscal rules and enhanced surveillance was a necessary step forward for sustaining the credibility of the single European currency, further reforms focusing on deepening European integration are still needed.
Keywords: 330